Incidence of General Didactics in the Teaching Learning Process of Foreign Languages in Cuba - Martínez-Linares, Carlos (Íkala, Revista de Lenguaje y Cultura, 2017)
The main goal in this article is to demonstrate students and colleagues of the pedagogical specialty in foreign languages, the need to consider the contributions of general didactics, which according to the author, are key elements for the fulfillment of teaching-learning objectives as stated in the official documents by the Ministry of Education of Cuba. The aim is to explain how these principles were implemented in accordance to the context under a scientific and integrated vision.